(untitled) (Psychology Travelogs, 2025)
The article analyzes and summarizes modern scientific concepts of the psychological well-being of the individual. It was found that psychological well-being is a multidimensional phenomenon that determines an individual’s ability to adapt to stressful and crisis conditions, maintain emotional stability, interact effectively with the social environment, and realize life goals. Structural components of psychological well-being including internal resources of the individual (sustainability, self-acceptance, competence, emotional stability) and external factors of the environment (social support, family and professional relationships, economic conditions) have been identified. It is shown that the specified components of psychological well-being are in dynamic interaction and can be actualized in different ways depending on life circumstances and social context. The main approaches to the study of psychological well-being are outlined, including integrative models of foreign and Ukrainian scientists, hedonic and eudemonic concepts, the theory of self-determination, and approaches to psychometric evaluation. It has been proven that the level of psychological well-being depends on the interaction of personal resources and the social environment, and its development contributes to increasing the adaptability, stability and life efficiency of the individual. Emphasis is placed on the practical significance of the results of the research on psychological well-being for the socio-psychological support of the individual in the conditions of social transformations and increased stress loads. Further directions of research are proposed, in particular, the development of contextually sensitive models of psychological well-being for various social groups and the improvement of methods of its comprehensive assessment.